Grafting as an effective approach for improvement of eggplant resistance against bacterial wilt (Ralstonia solanacearum) in screen-house condition - Musa, Ibrahim; Rafii, M.Y.; Khairulmazmi, Ahmad; Ramlee, ShairuI; Md Hatta, Muhammad Asyraf; Magaji, Usman; Chukwu, S.C.; Adetutu, Awosan Elizabeth (Taylor and Francis Ltd., 2024)
Forty-two accessions of eggplant were screened against Ralstonia solanacearum in screen-house environments. This was followed by an assessment of the genetic diversity of the 42 eggplant successions originating from Bangladesh, China, Thailand and Malaysia, accomplished by exploring SSR markers for germplasm characterisation. Five selected resistant genotypes used as a rootstock were further assessed with UPMSE16 strain in a subsequent trial. The pathogenicity test based on area under the disease progress curve (AUDPC) and disease severity index (DSI) at four weeks after inoculation indicated that genotypes TB3, TB6, TB7, MB16 and BB9 had the greatest degree of resistance. Also, the results of the second trial for grafted and control plants based on DSI and AUDPC at 4 WAI showed that grafted plants had resistance to UPMSE16 strain with no symptoms at 4 WAI. The 42 accessions were grouped into nine major clusters based on SSR markers using Unweighted Pair Group Method with Arithmetic mean. Hence, the phenotyping screening reveals that five eggplant accessions were resistant to R. solanacearum and can be used as potential rootstock. As a result, the discovered SSR markers may be effective in marker-assisted selection for future use in developing new rootstock.